In vitro Propagation of Ionidium suffruticosum Ging. ? A Seasonal Multipotent Medicinal Herb. - Sonappanavar, Arunkumar B.; Jayaraj, M.; Bagadekar, Asha N.; Bhandarkar, Anant V. (Plant Tissue Culture and Biotechnology, 2010)
Indirect regeneration of plant was obtained through organogenesis in leaf callus cultures of Ionidium suffruticosum. Leaf explants were found to be best suited for callus induction on MS with 2, 4-D (0.5 and 1.0 mg/l). Maximum shoot regeneration was obtained in MS supplemented with Kn (4.0 mg/l) alone and NAA (0.4 mg/l) with Kn (2.0 m/l). The in vitro shoots thus obtained were successfully rooted in MS supplemented with Kn (4.0 mg/l) alone and with NAA (2.0 mg/l) and Kn (0.2 mg/l). Seventy per cent of the rooted plants survived and they were successfully acclimated in soil. Key words: Ionidium suffruticosum, micropropagation, Medicinal herb D.O.I. 10.3329/ptcb.v19i2.5431 Plant Tissue Cult. & Biotech. 19(2): 143-150, 2009 (December)